2018
DOI: 10.1039/c8tb01382a
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandin vivotoxicity evaluation of halloysite nanotubes

Abstract: Halloysite is weakly toxic to cells and can be excreted out through the gastrointestinal metabolism of zebrafish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 60 publications
3
48
0
Order By: Relevance
“…Due to their morphological characteristics, halloysite nanotubes are efficient as catalytic supports [ 34 , 35 , 36 , 37 ], adsorbents of pollutants [ 38 , 39 ] and nanocarriers for functional molecules with biological [ 40 , 41 , 42 , 43 , 44 , 45 ] and chemical activities [ 46 , 47 , 48 , 49 ]. In this regards, it should be highlighted that halloysite is suitable for biomedical and pharmaceutical applications because of its biocompatibility and low toxicity, which was observed to both unicellular and multicellular organisms [ 50 , 51 , 52 , 53 , 54 ]. Interestingly, the inside/outside surfaces of halloysite are oppositely charged within the pH interval between 2 and 8 [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their morphological characteristics, halloysite nanotubes are efficient as catalytic supports [ 34 , 35 , 36 , 37 ], adsorbents of pollutants [ 38 , 39 ] and nanocarriers for functional molecules with biological [ 40 , 41 , 42 , 43 , 44 , 45 ] and chemical activities [ 46 , 47 , 48 , 49 ]. In this regards, it should be highlighted that halloysite is suitable for biomedical and pharmaceutical applications because of its biocompatibility and low toxicity, which was observed to both unicellular and multicellular organisms [ 50 , 51 , 52 , 53 , 54 ]. Interestingly, the inside/outside surfaces of halloysite are oppositely charged within the pH interval between 2 and 8 [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…44,45 This was also confirmed in in vivo studies on nematodes 46 and zebrafish. 47 The effect of HNTs on cells is dose-dependent as has been shown for human cell lines. 48 Recently, the size-dependent character of cellular internalisation of HNTs (250-650 nm in length) has been demonstrated in colon cancer cells.…”
Section: Clay-based Nanomaterialsmentioning
confidence: 89%
“…The authors demonstrated that HNTs promote the hatchability of zebrafish embryos and did not affect the morphological development at a concentration of ≤25 mg mL −1 . HNTs accumulated predominantly in the gastrointestinal tract of zebrafish larvae similar to nematodes …”
Section: Biocompatibility Of Halloysite Nanotubesmentioning
confidence: 99%